Gambaran histopatologik ginjal wistar yang diberi ekstrak binahong pasca pemberian gentamisin - Rajak, Zularsil F.W.; Loho, Lily; Lintong, Poppy (e-Biomedik, 2016)
Abstract: Kidney damage can be caused by many things, such as hypovolemia, sepsis, acute glomeluronefritis, rhabdomyolysis and drugs (gentamicin and NSAID). Gentamicin is an broad spectrum antimicrobial with high toxicity. Gentamicin is an aminoglycoside antibiotic known to be toxic to the kidneys and the side effects that gentamicin cause are renal tubular damage. There are many kinds of herbal plant in Indonesia with benefit, one of them is the binahong plants. Binahong (Anredera cordifoli (Ten) Steenis), has a high antioxidant that is equal to 9.614% of the compound flavonoid.5 Antioxidant contained in binahong leaves can be said as nefroprotective on kidney function. This study aims to reveal the renal histopathologic of wistar rat that have administered binahong extract after gentamicin administration. This study was an experimental study using 25 wistar rats that were divided into 5 groups. Group A is the negative control group (terminated the 7th day), while group B, C, D and E (the treatment group) were administered gentamicin 0.3 ml/day for 6 days. After administration of gentamicin, group B immediately terminated (day 7), group C were administered 50 mg/day of binahong extratct for 3 days (terminated on day 10), group D were administered 100 mg/day of binahong extract for 3 days (terminated on day 10), group E were administered gentamicin for 6 days (terminated on day 10). The results showed that the renal histopathological of wistar rats group that were administered gentamicin for 6 days, showed swelling and necrotic tubular epithelial cells. Wistar rats group that were administered of binahong showed regeneration of renal tubular epithelial cells. Conclusion: The administration of Gentamicin with toxical dose or 0.3 ml/day for 6 days showed acute tubular necrosis. Regeneration of renal tubular epithelial cells is better in the group that were administered binahong extract than the group that were administered pellets. Renal histopathologic of wistar rats at administration of binahong extract with dose of 100 mg are better compared to 50 mg. Keywords: gentamicin, binahong extract, histopathologogical image of wistar ratâ€™s kidneyÂ Abstrak: Kerusakan ginjal dapat disebabkan oleh berbagai hal, seperti hipovolemia, sepsis, glomeluronefritis akut, rabdomiolisis dan obat-obatan (Gentamisin dan NSAID). Gentamisin tergolong antibiotika (aminoglikosida) yang berspektrum luas dan memiliki toksisitas tinggi. Salah satu efek toksik dari gentamisin adalah menyebabkan kerusakan pada tubulus ginjal. Ada berbagai jenis tanaman herbal di Indonesia yang mempunyai khasiat, salah satunya adalah tanaman binahong, Tanaman binahong (Anredera cordifoli (Ten) Steenis), memiliki antioksidan yang cukup tinggi yaitu sebesar 9,614% senyawa flavonoid. Antioksidan yang terkandung dalam daun binahong dapat dikatakan sebagai nefroprotektif terhadap fungsi ginjal. Penelitian ini bertujuan untuk mengetahui gambaran histopatologik ginjal tikus wistar yang diberi ekstrak binahong pasca pemberian gentamisin. Penelitian ini merupakan penelitian eksperimental yang menggunakan 25 ekor tikus wistar yang dibagi dalam 5 kelompok. Kelompok A merupakan kelompok kontrol negatif (diterminasi pada hari ke-7), sedangkan kelompok B, C, D dan E (kelompok perlakuan) diberi gentamisin 0,3 ml/hari selama 6 hari. Setelah pemberian gentamisin, kelompok B langsung diterminasi (hari ke-7), kelompok C diberi ekstrak binahong 50 mg/hari selama 3 hari (diterminasi pada hari ke-10), kelompok D ekstrak binahong 100 mg/hari selama 3 hari (diterminasi pada hari ke-10). kelompok E diberi gentamisin selama 6 hari (diterminasi pada hari ke-10). Hasil penelitian menunjukkan bahwa kelompok tikus yang diinduksi gentamisin selama 6 hari secara histopatologik memperlihatkan adanya pembengkakan dan nekrosis sel epitel tubulus. Kelompok tikus yang diberi ekstrak binahong menunjukkan regenerasi sel epitel tubulus ginjal Simpulan: Pemberian gentamisin injeksi dosis toksik yaitu 0,3 ml setiap hari selama 6 hari menunjukkan nekrosis tubular akut (NTA). Regenerasi sel epitel tubulus ginjal lebih baik pada kelompok yang diberi ekstrak binahong dibandingkan kelompok yang hanya diberi pelet. Gambaran histopatologik ginjal lebih baik pada pemberian binahong dengan dosis 100 mg dibandingkan dosis 50 mg.Kata kunci: gentamisin, ekstrak binahong, gambaran histopatologik ginjal.